STUDENTS’ APOLOGY REALIZATION PATTERNS IN ONLINE CLASSES DURING THE PANDEMIC-19 - Ella Masita (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Online class becomes a more common platform in academic activities nowadays, specifically in during the Pandemic-19. As a consequence, equipping students with adequate skills is an urgent thing to do in order to prepare them in the world of digital citizenship.  This paper, then, is intended to investigate the common patterns made by university students in expressing their apology realization through the lens of Cross-Cultural Speech Act Realization Pattern (CCSARP).  It is expected that the identification of the patterns will enable lecturers to gain more comprehensive understanding as well as to help students any possible varieties in expressing apology.